Program Leaders’ New Tools for Outcomes Assessment and Improvement - JACQUELINE KRESS (Academic Chairpersons Conference Proceedings, 2017)
Academic leaders are expected to build cultures of inquiry and continuous improvement. This session provides practical examples of teacher-as-researcher tools, such as policy audits, Pareto charts, affinity exercises, curriculum control files, and data review calendars, that academic leaders can use to meet new demands for evidence-based decisions.
Keywords: leadership skills; data analysis; evidence; consensus; reporting